Women’s Involvements in Immoral Activities and the Development of Blissful Life - Ismail, , Abdul Munir (International Journal of Psychosocial Rehabilitation, 2020)
Purpose of the Study—This study aims to discuss issues regarding women’s involvement in vices or immoral activities and to recommend means to bring them back into the fold of local societies. The women recruited in this study, were homeless, beggars, drug addicts, and sex workers in Kuala Lumpur. Their involvements in such activities need to be addressed to ensure their safety and to protect the reputation of the city of Kuala Lumpur among tourists. Methodology:This study was based on a qualitative approach involving face-to-face interviews and observations of the life patterns of the research subjects in several locations in Kuala Lumpur, namely Chow Kit Road, Kampong Bahru, Kuala Lumpur Central, and Pudu Raya. Seven women were selected to be the interviewees after several rounds of negotiations to encourage them to share their experiences. To protect their privacy, their actual identities were not disclosed and they were referred to using identity codes (from R1 to R7). Main Findings: The findings showed several factors that contributed to their involvement in immoral activities, such as family breakdowns, infighting among family members, a lack of knowledge, poor education, and bad influences. Also, poverty, family conflicts, and poor understanding of Islamic teaching. As such, it is the responsibility of the society to provide them counsel and moral support and to take care of their financial and religious needs so that they can have a better place to live and to learn to live as true practicing Muslims. Applications: The findings can provide greater insight into the understanding of the plights of unfortunate women involved in immoral activities and identify factors that contribute to such involvements. Such findings can guide the stakeholders, such as religious officers and rehabilitation officers, to help such women to make amend and return to the fold of societies with care and compassion. Novelty: The finding can help the Ministry of Women, Family and Community Development (abbreviated in Malay as KPWKM) to formulate effective strategy in helping women who were forced to live an immoral life as a result of social decadence, who have largely been left out from the mainstream society. .